1997
DOI: 10.1128/jvi.71.4.3357-3362.1997
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sialic acid-galactose linkages in the chicken egg amnion and allantois influence human influenza virus receptor specificity and variant selection

Abstract: Human influenza viruses are more efficiently isolated by inoculating patient samples into the amniotic rather than the allantoic cavity of embryonated chicken eggs. This type of cultivation selects virus variants with mutations around the hemagglutinin (HA) receptor binding site. To understand the molecular basis of these phenomena, we investigated the abundances of sialic acid (SA) linked to galactose (Gal) by the ␣-2,3 linkage (SA␣2,3Gal) and SA␣2,6Gal in egg amniotic and allantoic cells and in Madin-Darby c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(64 citation statements)
references
References 34 publications
(36 reference statements)
1
63
0
Order By: Relevance
“…The apparent reduced ability of VicS-del to infect host cells does not necessarily indicate a loss of pathogenicity, but could indicate an altered capacity to bind to different cell receptors. It has been suggested that changes near the receptor binding domain of the S1 protein could modify the affinity of coronaviruses for different cell surface glycoproteins [57][58][59]. Potentially, the variations found in the S1 gene might have reduced the ability of VicS-del to infect respiratory tract cells, but not its ability to infect the cells of the chorioallantoic membrane (CAM) (where replication of IBV initially occurs in embryonated chicken eggs).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent reduced ability of VicS-del to infect host cells does not necessarily indicate a loss of pathogenicity, but could indicate an altered capacity to bind to different cell receptors. It has been suggested that changes near the receptor binding domain of the S1 protein could modify the affinity of coronaviruses for different cell surface glycoproteins [57][58][59]. Potentially, the variations found in the S1 gene might have reduced the ability of VicS-del to infect respiratory tract cells, but not its ability to infect the cells of the chorioallantoic membrane (CAM) (where replication of IBV initially occurs in embryonated chicken eggs).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Madin-Darby canine kidney (MDCK) cell lines are widely available, easily amplify in culture, and are commonly used for isolating IAVs from a variety of species. 12,14 Previous studies indicated that MDCK cells cultured in the presence of fetal bovine serum (FBS) express both α-2,6-linked and α-2,3-linked SA receptor types and showed that some cells co-express both receptors. 9,14 In contrast, another study found that 98% of MDCK cells adapted to serum-free media (SFM) expressed only α-2,6linked SA receptors, with 2% of cells expressing both α-2,3-and α-2,6-linked SA receptors.…”
Section: Thousands Of People Become Infected With Seasonally Circulatingmentioning
confidence: 99%
“…12,14 Previous studies indicated that MDCK cells cultured in the presence of fetal bovine serum (FBS) express both α-2,6-linked and α-2,3-linked SA receptor types and showed that some cells co-express both receptors. 9,14 In contrast, another study found that 98% of MDCK cells adapted to serum-free media (SFM) expressed only α-2,6linked SA receptors, with 2% of cells expressing both α-2,3-and α-2,6-linked SA receptors. 15 However, detailed characterization of SFM-adapted MDCK cells is needed because variations in SFM preparations may cause the cells to express different amounts of each SA receptor, altering IAV culture success.…”
Section: Thousands Of People Become Infected With Seasonally Circulatingmentioning
confidence: 99%
“…It has been shown that serial passage using chicken embryos enforces the selection of adapted viruses and inevitably alters the genetic codes of the primary viral isolates, especially for genes involved in cell adsorption and viral replication [8,9]. The environment of the viral replication may also selectively modify the original cell tropism and pathogenesis of the isolated virus [15,25]. It has been shown that a serially embryo-passaged of infectious bronchitis viruses (IBV) M41 strain exhibited significantly attenuated pathogenesis within the oviduct compared to the parental strain [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, egg-mediated epitope alterations in amplified isolates might attenuate the protective efficiency of these viruses when used to vaccinate against the challenge of a wild-type virulent strain [16,24]. For instance, after egg adaption, human influenza A virus, originally showing a2-6 sialic acid tropism only, exhibits increased hemagglutinin (HA) binding affinity to a2-3 sialic acid-containing gangliosides due to amino acid substitutions in the vicinity of the receptor binding site of the HA protein [8,15]. For primary viral isolates, providing natural host cells for replication might eliminate the selection pressure of an exotic growth environment and avert the alteration of cell tropism and consequent genomic mutations.…”
Section: Introductionmentioning
confidence: 99%